The effectiveness of cellulolytic bacteria on feeds towards the immune response of Tilapia - Dony Prasetyo; Anis Zubaidah; Hany Handajani; Emilio Hudin (IJOTA (Indonesian Journal of Tropical Aquatic), 2022)
Tilapia is one of fishery commodities that is very good to be developed in thecultivation sector. However, the tilapia often incurs with the diseases so thatthe cultivators have difficulty in maintaining the health of the tilapia. One ofthe ways to improve the health is by distributing the cellulolytic bacteriaaddition and blood is one of parameters that used to identify the tilapia’shealth. The research method used was an experimental quantitative methodby preserving the fish and giving cellulolytic bacteria on the feeds for 30 days;then, the bloods ware taken to test the immune system. The parameters usedwere 12 parameters, of which parameters involved of 8 main parameters andsupporting parameters. The conclusion of this research is that the besttreatments are in the treatments of P1 because 4 main parameters out of 8main parameters experience an increasement and 6 main parametersexperience highest increasement from all of the treatments. For the P3, thehighest increasement of main immune system is in the leukocytes andphagocytosis activity. Thus, the fish can prevent the outside attacks.